Moving beyond “believers vs. deniers” labels: a public response-centered framework for energy justice in the emerging renewable energy sector - Kunlere, Idowu O.; Shah, Kalim U. (Frontiers in Sustainable Energy Policy, 2024)
The global shift toward renewable energy raises concerns that the legacy of energy injustice—historical imbalances in the distribution of benefits and burdens from fossil fuels—may persist within renewable systems intended to address climate change. Current research highlights that energy injustice could threaten the success of this transition, yet limited focus has been placed on understanding public responses to these emerging injustices. Existing frameworks often reduce public opinion to simplistic binaries (for example, “supporters vs. opponents”), which fail to capture the nuanced and diverse perspectives necessary for a comprehensive understanding of public sentiment on energy issues. To address this, we introduce the “PARO framework,” a novel tool that categorizes public responses to energy injustice within the renewable energy context. The PARO framework broadens the analytical lens on public opinion, offering insights that can guide more targeted and effective solutions for promoting equitable energy transitions.